The effect of vitreomacular adhesion in exudative age-related macular degeneration on the results of ranibizumab intravitreal injection - Suzuki H (Dove Medical Press, 2017)
Hiroyuki Suzuki,1 Seita Morishita,1 Ryohsuke Kohmoto,1 Masanori Fukumoto,1 Takaki Sato,1 Teruyo Kida,1 Mari Ueki,1 Hidehiro Oku,1 Kimitoshi Nakamura,2 Tsunehiko Ikeda1 1Department of Ophthalmology, Osaka Medical College, Takatsuki-City, Osaka, Japan; 2Nakamura Eye Clinic, Matsumoto-City, Nagano, Japan Purpose: To investigate whether vitreomacular adhesion (VMA) affects the outcome of anti-vascular endothelial growth factor (VEGF) therapy for the treatment of exudative age-related macular degeneration (AMD) in Japanese patients. Subjects and methods: Of 88 Japanese AMD patients (28 men and 60 women, mean age: 72.7±7.5 years) who underwent intravitreal injection of ranibizumab for 3 years from 2010 to 2013, this study involved 12 eyes of 12 patients (10 men and two women) in whom VMA was observed based on optical coherence tomography (OCT) findings (VMA [+] group) and 17 eyes of 16 patients (seven men and nine women, control group) in whom no VMA was observed (VMA [-] group). In all enrolled patients, ranibizumab was administered monthly for 3 months, and then administered as needed (ie, pro re nata) when deterioration was observed. The two groups were then compared in regard to changes in visual acuity (VA) and the frequency of ranibizumab administration over a 1-year period. Results: No significant difference was found between the two groups in regard to the transformation of the mean logarithm of the minimum angle of resolution VA change after the first visit. Over the 1-year treatment, the mean frequency of ranibizumab administration for the VMA (+) group was 5.6±2.5 times and for the VMA (-) group was 3.8±1.1 times, thus illustrating a significant difference between the two groups (Mann–Whitney’s U-test: P<0.05). Conclusion: Our findings show that the mean frequency of ranibizumab administration for the VMA (+) group was higher than that in the VMA (-) group, thus indicating that VMA might possibly be involved in the progress of AMD pathology. Keywords: age-related macular degeneration, vitreomacular adhesion, anti-VEGF therapy, ranibizumab, optical coherence tomography